Improvement in mechanical properties of NBR/LiClO4/POSS nanocomposites by constructing a novel network structure. (18th January 2017) - Yang, Shuyan; Fan, Hongbo; Jiao, Yuanqi; Cai, Zhuodi; Zhang, Peng; Li, Yangping
Abstract: The mechanical properties and the possible micro-structure of nitrile-butadiene rubber/lithium perchlorate/polyhedral oligomeric silsesquioxane (NBR/LiClO4 /POSS) nanocomposites have been investigated thoroughly. The interactions among Li + cations, CN groups and COC groups bring in a novel network structure consisting of several kinds of effective crosslinks, causing an increase in the glass transition temperature of POSS, as well as in the crosslink contribution ( G c ) and the constraint contribution ( G e ), which facilitates strong interface cohesion between POSS and NBR matrix and a well dispersion of POSS. The addition of POSS not only increases the crosslinking density of NBR/LiClO4 /POSS nanocomposites, but also improves the 300% modulus and tensile strength greatly. Therefore, a possible micro-structure has been proposed to express the experimental observation.